Proposal of a climate-tourism index adapted to inland tourism in the Iberian Peninsula: applied to the city of Madrid - Alfredo Millán López; Felipe Fernández García (Investigaciones Geográficas)
In the 1990s, in the case of Spain, a new concept of tourism emerges that is very different from the classic one of the coast —known as sun and beach tourism—. This tourism, which is called inland tourism, encompasses a broad spectrum of activities and resources —cultural, heritage, natural, urban, rural, business ...— and it has had a major role in a boom in recent years, precisely because the value of all these resources has been enhanced. But there is a potential resource that until now has not been taken into account when preparing studies on inland tourism in Spain: the climate resource and its influence on the comfort of tourists. This paper presents the development and implementation of a climate-tourism index, called ICTI (Indoor Tourist Climate Index) compiled using Mieczkowski's Tourism Climate Index (TCI) (1985). It is a process of adaptation to inland tourism in the Iberian Peninsula, which is intended to verify its possibilities and limitations for the evaluation of the climate and its influence on this type of tourism. This index analyzes and characterizes the climate-tourism suitability model of the city of Madrid and the climate as an indicator of the tourism potential of an inland destination.